Case studies used in construction to achieve specific learning outcomes: The case of the embankments constructed for the approach to Limerick Tunnel, Ireland - ORR, TREVOR (University of Missouri, 2013)
This paper gives an example of a case study written for instructional purposes, in order to support the achievement of specific learning outcomes which include (i) identifying modes of failure and (ii) selecting appropriate soil parameter types and values. Case writing was based primarily on information from a detailed publicly available article, supplemented with additional input from one author of this article. The case narrative is accompanied by annotated calculations, which follow the general design philosophy of the project. The case focuses on two of the main issues for the geotechnical design of the highway embankments close to the Limerick Tunnel, which are founded on very soft organic fine grained material. First, secondary compression, which is sizeable for this highway project, required surcharging to reduce the rate of long-term settlement. Second, the low undrained shear strength and high compressibility of the foundation material required construction of the embankments in stages, to achieve a degree of consolidation necessary for increased vertical effective stress, increased shear strength and reduced compressibility. This paper includes the case narrative, excerpts from the accompanying calculations, and comments on the instructional decisions involved in the preparation of both.
7th International Conference on Case Histories in Geotechnical Engineering
PUBLISHED
This paper gives an example of a case study written for instructional purposes, in order to support the achievement of specific learning outcomes which include (i) identifying modes of failure and (ii) selecting appropriate soil parameter types and values. Case writing was based primarily on information from a detailed publicly available article, supplemented with additional input from one author of this article. The case narrative is accompanied by annotated calculations, which follow the general design philosophy of the project. The case focuses on two of the main issues for the geotechnical design of the highway embankments close to the Limerick Tunnel, which are founded on very soft organic fine grained material. First, secondary compression, which is sizeable for this highway project, required surcharging to reduce the rate of long-term settlement. Second, the low undrained shear strength and high compressibility of the foundation material required construction of the embankments in stages, to achieve a degree of consolidation necessary for increased vertical effective stress, increased shear strength and reduced compressibility. This paper includes the case narrative, excerpts from the accompanying calculations, and comments on the instructional decisions involved in the preparation of both.
Chicago, USA
Keywords: case study, learning outcomes, embankment, soft ground, settlement